THE IMPACT OF FINANCIAL PERFORMANCE OF MERAH PUTIH VILLAGE COOPERATIVES ON REGIONAL REVENUE ENHANCEMENT IN SIDOARJO REGENCY - Siti Samsiyah; Yuli Kurnia F; Yusuf Iskandar; Bisma Arianto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study analyzes the impact of the financial performance of Merah Putih Village Cooperatives (KDMP) on regional revenue enhancement in Sidoarjo Regency. Using quantitative analysis with descriptive statistics and simple linear regression, this research evaluates liquidity, profitability (ROA), solvency, and SHU contribution. The results indicate strong liquidity and solvency, but declining profitability. Regression results show financial performance has a positive and significant effect on SHU, implying cooperatives play a strategic role in strengthening local revenue. This study provides policy implications for improving cooperative efficiency and regional fiscal capacity.